Avengers assembly : Orientation - Chhibber, Preeti (Avengers., 2020)
Kamala Khan, Miles Morales, Doreen Green, America Chavez, and other young Marvel heroes join forces to defeat . . . the academic decathlon? Welcome to the Avengers Institute!.